Management of archival literary sources: the Greek approach. Issue 1 (November 2018) - Minotos, Marietta; Koulikourdi, Anna
Abstract : In Greece, as in many other countries, literary archives play an important role in the intellectual, social, political and cultural life of the country and are interconnected with the history of the state. Since the phenomenon of the diaspora of literary archives is familiar to all literary researchers, the scope of this article is to promote awareness of literary archives in Greece and to provide an approach to literary sources in an exceptionally wide range of archival institutions. It takes into account the Greek historical background in literary traditions and connects it with the current intensive interest in the archives, the legal framework, the principles of access to archival material and the challenges of on-line access for this category of archives and archivists.